Factor VIII : C and Factor VIII R: Ag in Argentine Hemorrhagic Fever - Molinas, Felisa C; Maiztegui, Julio I (Thrombosis and Haemostasis, 1981)
Factor VIII procoagulant activity (F VIII: C) and factor VIII related antigen (F VIII R: Ag) were investigated in 35 patients with Argentine hemorrhagic fever. Since the results obtained in the three clinical forms of the disease were not significantly different, they were tabulated altogether. F VIII: C was low in early stages of the disease but increased progressively in later days (days 5–6:0.54 ± 0.10 I.U./ml; days 13–14:0.95 ± 0.13 I.U./ml). In contrst, the levels of F VIII R: Ag were high all along the disease and they returned to normal values during the convalescence period (days 5–6; 2.58 ± 0.54 I.U./ml; day 30: 1.30 ± 0.14 I.U./ml). The levels of F VIII R: Ag were similar in samples drawn before (11 cases) or after (10 cases) the treatment with immune plasma infusion. Plasma samples from 12 patients were studied by two-dimensional immunelectrophoresis. The only abnormality found was increased height of the immune precipitation arc.
Keywords: F VIII: C–F VIIIR: Ag; Argentine hemorrhagic fever